Red Blood Cell Distribution Width Is a Predictive Factor of Anthracycline-Induced Cardiotoxicity - Yaegashi, Daiki; Oikawa, Masayoshi; Yokokawa, Tetsuro; Misaka, Tomofumi; Kobayashi, Atsushi; Kaneshiro, Takashi; Yoshihisa, Akiomi; Nakazato, Kazuhiko; Ishida, Takafumi; Takeishi, Yasuchika (Frontiers in Cardiovascular Medicine, 2020)
Background: Red blood cell distribution width (RDW) is associated with prognosis in widespread cardiovascular fields, but little is known about relationship with the onset of cancer therapeutics-related cardiac dysfunction (CTRCD). Objectives: The purpose of this study was to assess whether RDW could predict the onset of CTRCD by anthracycline. Methods: Consequential 202 cancer patients planed for anthracycline treatment were enrolled and followed up for 12 months. The patients were divided into 2 groups based on the median value of baseline RDW before chemotherapy [low RDW group, n = 98, 13.0 [12.6–13.2]; high RDW group, n = 104, 14.9 [13.9–17.0]]. Cardiac function was assessed serially by echocardiography at baseline (before chemotherapy), as well as at 3, 6, and 12 months after chemotherapy with anthracycline. Results: Baseline left ventricular end systolic volume index and ejection fraction (EF) were similar between two groups. After chemotherapy, EF decreased at 3- and 6-month in the high RDW group [baseline, 64.5% [61.9–68.9%]; 3-month, 62.6% [60.4–66.9%]; 6-month, 63.9% [60.0–67.9%]; 12-month, 64.7% [60.8–67.0%], P = 0.04], but no change was observed in low RDW group. The occurrence of CTRCD was higher in high RDW group than in low RDW group (11.5 vs. 2.0%, P = 0.008). When we set the cut-off value of RDW at 13.8, sensitivity and specificity to predict CTRCD were 84.6 and 62.0%, respectively. Multivariable logistic regression analysis revealed that baseline RDW value was an independent predictor of the development of CTRCD [odds ratio 1.390, 95% CI [1.09–1.78], P = 0.008]. The value of net reclassification index (NRI) and integrated discrimination improvement (IDI) for detecting CTRCD reached statistical significance when baseline RDW value was added to the regression model including known risk factors such as cumulative anthracycline dose, EF, albumin, and the presence of hypertension; 0.9252 (95%CI 0.4103–1.4402, P < 0.001) for NRI and 0.1125 (95%CI 0.0078–0.2171, P = 0.035) for IDI. Conclusions: Baseline RDW is a novel parameter to predict anthracycline-induced CTRCD.